High-resolution synchrotron X-ray analysis of bioglass-enriched hydrogels - Shkarina, Svetlana; Douglas, Timothy E. L.; Samal, Sangram K.; Detsch, Rainer; Cholewa‐Kowalska, Katarzyna; Braeckmans, Kevin; Boccaccini, Aldo R.; Skirtach, Andre G.; Weinhardt, Venera; Baumbach, Tilo; Surmeneva, Maria A.; Surmenev, Roman A. (Journal of biomedical materials research, 2016)
Enrichment of hydrogels with inorganic particles improves their suitability for bone regeneration by enhancing their mechanical properties, mineralizability, and bioactivity as well as adhesion, proliferation, and differentiation of bone-forming cells, while maintaining injectability. Low aggregation and homogeneous distribution maximize particle surface area, promoting mineralization, cell-particle interactions, and homogenous tissue regeneration. Hence, determination of the size and distribution of particles/particle agglomerates in the hydrogel is desirable. Commonly used techniques have drawbacks. High-resolution techniques (e.g., SEM) require drying. Distribution in the dry state is not representative of the wet state. Techniques in the wet state (histology, µCT) are of lower resolution. Here, self-gelling, injectable composites of Gellan Gum (GG) hydrogel and two different types of sol-gel-derived bioactive glass (bioglass) particles were analyzed in the wet state using Synchrotron X-ray radiation, enabling high-resolution determination of particle size and spatial distribution. The lower detection limit volume was 9 × 10−5 mm3. Bioglass particle suspensions were also studied using zeta potential measurements and Coulter analysis. Aggregation of bioglass particles in the GG hydrogels occurred and aggregate distribution was inhomogeneous. Bioglass promoted attachment of rat mesenchymal stem cells (rMSC) and mineralization. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 1194-1201, 2016.